The Influence of Credit Guarantees on the Growth of Micro, Small, and Medium Enterprises (MSMEs) in Kupang City - Handu, Variani Setia; Ballo, Fransina W; Tomasowa, Olivia L.E (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
Credit guarantee is a strategic effort to improve access to financing for Micro, Small, and Medium Enterprises (MSMEs) in Kupang City. This study aims to examine the influence of credit guarantees on the growth of MSMEs in Kupang City and analyze how the implementation of credit guarantees can strengthen business performance, increase sales, and profit for MSME actors. This research employs a quantitative approach with data collected through surveys and documentation from MSME actors who have received credit guarantees. The results indicate that credit guarantees have a positive and significant effect on the growth of MSMEs in Kupang City. Prior to obtaining guarantees, MSME actors faced obstacles in accessing capital, managing transactions, and developing their businesses, especially those just starting out. After receiving credit guarantees, MSME actors were able to overcome these barriers, enhance business capacity, and compete in the local market. The conclusions of this study affirm that credit guarantees are a crucial factor in driving MSME growth and supporting sustainable regional economic development.